2021
DOI: 10.1186/s12909-021-02700-0
|View full text |Cite
|
Sign up to set email alerts
|

Training interns in nutrition and dietetics: a cross-sectional study of the barriers and motivators to being a Registered Dietitian Nutritionist preceptor

Abstract: Background As is common across the health professions, training of Registered Dietitian Nutritionists (RDNs) requires experiential learning for interns/students to gain skills and demonstrate entry-level competency. Preceptors are essential to the experiential learning component of health care professional training, providing supervision and mentoring as students and interns gain the skills required for entry-level practice competency. Over the past 27 years, 47–73% of applicants to dietetic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Additional opportunities for recognition or appreciation were noted by Hutchins et al21 They found that only 35% of current preceptors indicated that there were adequate opportunities to share information with other preceptors 21. This may be another opportunity for preceptors to learn best practices for precepting while also recognizing those individuals with extensive experience.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional opportunities for recognition or appreciation were noted by Hutchins et al21 They found that only 35% of current preceptors indicated that there were adequate opportunities to share information with other preceptors 21. This may be another opportunity for preceptors to learn best practices for precepting while also recognizing those individuals with extensive experience.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5% of respondents indicated that they receive extra pay for precepting, while just over half indicated receiving insufficient compensation. Canadian and US dietitians similarly reported low frequencies for pay and compensation increases as well as workload decreases 17,21. Among current preceptors completing a national survey, only 6% indicated that precepting increases their chances of promotion and advancement 21.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations